Spanish campaign flyer for Jane Tolmach
This Spanish-language campaign flyer urges voters to elect Jane McCormick Tolmach to the State Assembly in the 36th District. It highlights her commitment to preventing the state from shifting tax burdens onto local residents, establishing a four-year college in Ventura County, promoting full employment, protecting the environment, strengthening conflict-of-interest laws, and addressing the insurance crisis. The flyer emphasizes her extensive public service experience, including roles as Oxnard City Council member and mayor, school board member, transportation and regional government leader, and longtime Democratic Party participant. It presents her as a dedicated public servant with the courage to resist special interests and calls on voters to support her on June 8.